Wafer-Scale Fabrication of Two-Dimensional PtS2/PtSe2 Heterojunctions for Efficient and Broad band Photodetection - Yuan, Jian; Sun, Tian; Hu, Zhixin; Yu, Wenzhi; Ma, Weiliang; Zhang, Kai; Sun, Baoquan; Lau, Shu Ping; Bao, Qiaoliang; Lin, Shenghuang; Li, Shaojuan (ACS applied materials & interfaces, 2018)
The fabrication of van der Waals heterostructures mainly extends to two-dimensional (2D) materials that are exfoliated from their bulk counterparts, which is greatly limited by high-volume manufacturing. Here, we demonstrate multilayered PtS2/PtSe2 heterojunctions covering a large area on the SiO2/Si substrate with a maximum size of 2″ in diameter, offering throughputs that can meet the practical application demand. Theoretical simulation was carried out to understand the electronic properties of the PtS2/PtSe2 heterojunctions. Zero-bias photoresponse in the heterojunctions is observed under laser illumination of different wavelengths (405–2200 nm). The PtS2/PtSe2 heterojunctions exhibit broad band photoresponse and high quantum efficiency at infrared wavelengths with lower bounds for the external quantum efficiencies being 1.2% at 1064 nm, 0.2% at 1550 nm, and 0.05% at 2200 nm, and also relatively fast response time at the dozens of millisecond level. The large area, broad band 2D heterojunction photodetector demonstrated in this work further corroborates the great potential of 2D materials in the future low-energy optoelectronics.